Retrospective observational study to compare Xpert MTB/RIF assay with other diagnostic tests in lymph node tuberculosis - Nithya Haridas; Asmita Mehta; Akhilesh Kunoor; Sadia Khan (Wolters Kluwer Medknow Publications, 2022)
Background: Lymph node tuberculosis (TB) is the most common form of extrapulmonary TB in India. Standards for TB care in India recommend microscopy/culture/CBNAAT/molecular test/histopathology examination and drug sensitivity testing on appropriate specimens from the presumed sites of involvement for all patients with presumptive extrapulmonary TB. Objectives: To analyze the utility of Xpert MTB/Rif assay in lymph node TB. Methods: All patients who underwent lymph node sampling between July 2014 and June 2017 and for whom Xpert MTB/Rif assay was done were included. Demographic profile, Xpert MTB/Rif assay result, histopathology/cytology findings, smear acid-fast bacillus (AFB), and AFB culture results were noted. A composite reference score (CRS) was made. Results: Xpert MTB/Rif assay was positive in 63 of the 81 patients. Xpert had a sensitivity of 82.14% and specificity of 86.18%when compared against AFB culture and 75.61% and 98.97% when compared against CRS. Conclusion: Xpert MTB/Rif assay is a valuable test for rapid diagnosis of lymph node TB.